HLA and MuSK‐positive myasthenia gravis: A systemic review and meta‐analysis. (7th May 2018) - Hong, Y.; Li, H.‐F.; Romi, F.; Skeie, G. O.; Gilhus, N. E.
Abstract : Objectives: Myasthenia gravis (MG) represents a spectrum of clinical subtypes with differences in disease mechanisms and treatment response. MG with muscle‐specific tyrosine kinase (MuSK) antibodies accounts for 1%‐10% of all MG patients. We conducted a meta‐analysis to evaluate the association between HLA genes and MuSK‐MG susceptibility. Subjects and methods: Studies were searched in Pubmed, EMBASE database and other sources between 2001 and 2018. Genotype, allele and haplotype frequencies of HLA loci in MuSK‐MG patients and healthy controls were extracted from each included study. Results: The meta‐analysis showed that HLA DQB1*05, DRB1*14 and DRB1*16 were strongly associated with an increased risk of MuSK‐MG ( P  <   .0001), whereas HLA DQB*03 was less frequent in MuSK patients compared with healthy controls ( P  <   .05). Haplotype analysis showed that these DQB1 and DRB1 alleles were closely linked, forming both risk (DQ5‐DR14, DQ5‐DR16, P  < .0001) and protective (DQ3‐DR4, DQ3‐DR11, P  < .05) haplotypes. Conclusion: The distinct genetic patterns of MuSK‐MG indicate that variation in HLA class II genes plays an important role in the pathogenesis of MuSK‐MG patients.